No Child Should Be Left Behind by COVID-19: A Report about the COVID-19 Pandemic Experience in Children and Adolescents with Acute or Chronic Disease Treated at a Pediatric Referral Hospital in Italy - Giulia Zucchetti; Sabrina Ciappina; Cristiana Risso; Alice Malabaila; Sara Racalbuto; Elena Longo; Margherita Dionisi Vici; Marina Bertolotti; Paola Quarello; Franca Fagioli (Pediatric Reports, 2023)
Background: The pandemic of coronavirus disease 2019 (COVID-19) was undoubtedly a stressful experience for everyone. General opinion believed that children with acute or chronic illness could experience additional burden, but this is not confirmed. The aim of this study is to understand how children and adolescents already suffering from acute or chronic illness (e.g., cancer, cystic fibrosis, neuropsychiatric disorders) feel about the COVID-19 pandemic, and if the experience is significantly different between these children and children without illness. Methods: Children and adolescents affected by acute or chronic illness (named the “fragile group”) treated at the Regina Margherita Children Hospital in Italy, were enrolled in the study by filling a questionnaire about their pandemic experiences. Also, a group of children and adolescents without acute or chronic illness (named the “low-risk group”) recruited in the emergency department of the hospital, participated in the study in order to compare experiences. Results: The study group was composed of 166 children and adolescents (Median age = 12 yrs; 78% fragile group, 22% low-risk group). Participants experienced a general state of fear of the virus and of a potential infection for both themselves and their families, while feelings and thoughts that interfere with daily functioning were less frequent. The fragile group seems to be more resilient towards the pandemic situation than low-risk group and some differences on the basis of the type of illness were found in the fragile group. Conclusions: Dedicated psychosocial intervention must be proposed in order to support fragile children and adolescents’ well-being during the pandemic, also on the basis of their clinical and mental history.